USULAN PERANCANGAN TATA LETAK DENGAN MENGGUNAKAN METODE AUTOMATED LAYOUT DESIGN PROGRAM (ALDEP) DAN COMPUTERIZED RELATIONSHIP LAYOUT PLANNING (CORELAP) PADA PT. POTECH INDO MANDIRI - Qhawila Balqis (2023)
Increasingly fierce industrial competition in industrial development requires companies to have good performance, including in the design of existing facilities to meet market demand. One important factor in the success of the company is an effective layout on the production floor. In this study, the Automated Design Layout Program (ALDEP) and Computerized Relationship Layout Planning (CORELAP) methods were used with the initial stage of making an Activity Relationship Chart (ARC). In this study, it was revealed that the company faced the problem of non-optimal layout, which caused fatigue in employees due to the long distance between departments. The results of the comparison of the two methods show that the fourth layout in the ALDEP method is the proposed layout option for the company. Thus, this research provides optimal layout recommendations for PT Potech Indo Mandiri, so that it is expected to increase the operational efficiency and productivity of the company in meeting increasing market demand.